2009
DOI: 10.1080/00218460903291486
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, Spreading, and Proliferation of Endothelial Cells on Charged Hydrogels

Abstract: As soft and wet scaffolds, hydrogels are attractive materials for tissue engineering due to their similarity in structure and properties to living tissue. For designing hydrogels as potential artificial tissues, some basic requirements, such as a high level of cellular viability, suitable viscoelasticity, and high mechanical strength are required. However, it is difficult to develop a hydrogel that satisfies even two of these requirements at the same time. In this review, our recent advances in developing synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…In a word, HCAECs cultured on hydrogels of optimal modulus have an excellent function against platelets adhesion while those on PS show a poor surface function. The result is consistent with the result of vein endothelial cells cultured on hydrogels reported by our previous investigation 34, 47…”
Section: Resultssupporting
confidence: 93%
“…In a word, HCAECs cultured on hydrogels of optimal modulus have an excellent function against platelets adhesion while those on PS show a poor surface function. The result is consistent with the result of vein endothelial cells cultured on hydrogels reported by our previous investigation 34, 47…”
Section: Resultssupporting
confidence: 93%
“…On gels with F < 0.4 (low charge density), endothelial cells had a small area, fast migration velocity, and showed less proliferation due to poor fibronectin adsorption, whereas on gels with F ¼ 0.4 or higher (high charge density), endothelial cells had a large area and were less mobile, reaching confluence on the gel surface. 34,36 On the basis of these results, we also assumed that the fast migration of NHAC-kn cells on neutral and low-charge-density hydrogels was due to poor fibronectin adsorption, which enhances the collision frequency between NHAC-kn cells and favors the vertical stacking of cells. The weaker adhesion of the gel favors the 3D stacking of the cells, which is similar to the behavior in vivo, and this promotes the redifferentiation of the cells.…”
Section: Spontaneous Redifferentiation Of Dedifferentiated Chondrocytmentioning
confidence: 89%
“…33 The double-network hydrogel surface was covered by a layer of the neutral polymer poly(N, N-dimethylacrylamide) (PDMAAm); the adherence of this polymer to the cells is probably weak yet suitable. 34 Considering that the chondrocytes are present in cartilages in a 3D manner, we assume that the dedifferentiation of chondrocytes to a fibroblastic phenotype on the 2D PS substratum is due to the very strong adhesion of the PS substratum to the cells. By tuning the interaction between the substratum and chondrocytes, we expect chondrocyte redifferentiation to occur on a 2D scaffold along with proper adhesion of the chondrocytes to the substratum.…”
Section: -29mentioning
confidence: 99%
“…28,29 Our previous studies have shown that the amount of negative charges of hydrogels has a substantial influence on the behaviors of cells. [30][31][32][33] It has been found that negatively charged hydrogels, such as poly(2-acrylamido-2-methylpropane sulfonic acid sodium salt) (PNaAMPS) and poly(sodium p-styrene sulfonate) (PNaSS), are suitable scaffolds for endothelial cell culture. When the gel was negatively charged with an absolute Zeta potential value higher than 20 mV, endothelial cells can adhere, spread, proliferate, and finally reach confluence on the gel surface, without any modification of cell adhesive protein.…”
Section: Introductionmentioning
confidence: 99%
“…When the gel was negatively charged with an absolute Zeta potential value higher than 20 mV, endothelial cells can adhere, spread, proliferate, and finally reach confluence on the gel surface, without any modification of cell adhesive protein. [30][31][32][33] On the other hand, the dedifferentiated chondrocytes can spontaneously be re-differentiated to chondrocytes cells on neutral and low-charge-density hydrogels. 34 Moreover, negatively charged gels can induce chondrogenic differentiation even in the insulin-free maintenance medium, while the neutral gels showed better performance for chondrogenic aggregation and differentiation when the inducible factors were added in the culture system.…”
Section: Introductionmentioning
confidence: 99%